Implementation of the Make A Match Learning Method to Improve Islamic Religious Education Learning Outcomes on Asmaul Husna Material for Class 4 State Elementary School Setting Batang Hari Leko District Musi Banyuasin Regency - Saparudin, Saparudin; Hidayah, Nurul; Fadhlun, Fadhlun (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Education is something that every human being must obtain. Every day the development of learning models for quality education becomes clearer, both at national and international levels. The development of education from year to year must be better, so that it is in line with the needs of the times which are always developing following the flow of globalization. Applying the Make a Match technique will further activate students in learning, making learning more meaningful because of active student involvement during the learning process. Through this method, students will also be trained to express ideas, opinions and criticism of other people. So it is hoped that it will be able to optimize student learning outcomes. The type of research used in this research is field research (Field Research) which is qualitative and quantitative in nature. With data collection techniques, namely interviews, observation and documentation. The results of this research are in the Implementation of the Make a Match Learning Method to Improve Islamic Religious Education Learning Outcomes in Asmaul Husna Material for Class 4 State Elementary School Setting Batang Hari Leko District, Musi Banyuasin Regency